2017
DOI: 10.1016/j.ijrobp.2017.01.140
|View full text |Cite
|
Sign up to set email alerts
|

CD8+/FOXP3+ Ratio and PD-L1 Expression Associated With Survival in pT3N0M0 Stage Esophageal Squamous Cell Cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…On the other hand, in a recent study, PD‐L1 expression was associated with a significantly worse prognosis in patients with SCC undergoing esophagectomy or definitive radio‐chemotherapy . In a different series, in patients with SCC who underwent surgery without preoperative therapy, high PD‐L1 expression was also associated with worse overall and relapse‐free survival . On the contrary, in patients undergoing surgery alone, PD‐L1 expression was positively associated with a better prognosis .…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, in a recent study, PD‐L1 expression was associated with a significantly worse prognosis in patients with SCC undergoing esophagectomy or definitive radio‐chemotherapy . In a different series, in patients with SCC who underwent surgery without preoperative therapy, high PD‐L1 expression was also associated with worse overall and relapse‐free survival . On the contrary, in patients undergoing surgery alone, PD‐L1 expression was positively associated with a better prognosis .…”
Section: Discussionmentioning
confidence: 85%
“…Immunohistochemical PD‐1 expression on lymphocytes was associated with the peritumoral reaction in tumours. In contrast to previous studies of patients with oesophageal cancer, the present study evaluated morphological components of lymphocytic reactions in a much larger patient cohort. Given that morphological lymphocytic reactions can be assessed by routine histopathological examination of resection specimens, these observations may have clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…A question that remains unanswered is whether subtyping of infiltrating lymphocytes would provide additional information beyond morphological or histopathological evaluation of lymphocytic reaction patterns. Previous studies of oesophageal cancer have reported that the presence of infiltrates or their localization by specific subtype of lymphocytes (such as CD8+, CD57+, FOXP3+ lymphocytes) is associated with patient outcome. On the other hand, other lymphocyte subsets, including CD3+, CD4+ or CD45RO+ lymphocytes, were not associated with patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations